PERMODELAN DAN ESTIMASI ENDAPAN NIKEL LATERITE PADA BLOCK CHARLIE DI PT TIMAH EKSPLOMIN UNIT NIKEL KABAENA KECAMATAN KABAENA BARAT, KABUPATEN BOMBANA, PROVINSI SULAWESI TENGGARA - Sundari, Woro (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2023)
The research area located in Baliara Village, West Kabaena District, Bombana Regency, Southeast Sulawesi Province has the potential for laterite nickel minerals that are quite prospect for mining. This is supported by the exploration and modeling of ore bodies which is the initial stage for mining. Exploration activities include drilling activities at locations that are suspected to have prospective laterite nickel ore content and conducting sample analysis in the laboratory, to determine the estimated levels at the research site. Modeling of the ore body was carried out to determine the shape of the ore body of laterite nickel ore at the research site. The modeled ore body will be a reference in carrying out mining activities. Exploration activities begin with drilling at the research site. The number of boreholes taken is 105 boreholes with a distance between boreholes of approximately 50 meters. The depth of the borehole ranges from 4.2 meters to 32 meters from the surface. For laboratory sample tests, samples are taken every 1 meter depth from each borehole. Using the conventional method, namely polygon, the area of influence in the calculation of nickel lateri resources in the Charlie Block, the tonnase is around 1195594.9 tons. Using surpac software the tonnase magnitude on Block Charlie is 3279775.4 Tons.